2014
DOI: 10.1590/s1980-57642014dn82000011
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and visuospatial executive functions in healthy elderly: The impact of education and frequency of reading and writing

Abstract: ObjectiveTo assess the predictive role of education and frequency of reading and writing habits (FRWH) on the cognitive flexibility, inhibition and planning abilities of healthy elderly individuals.MethodsFifty-seven healthy adults aged between 60 and 75 years with 2 to 23 years of formal education were assessed as to the frequency with which they read and wrote different types of text, as well as their number of years of formal education. Executive functions were evaluated using the Hayling Test and the Modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…This effect has been consistently reported in previous studies with the IFS [33,47,48] but also with other executive screening measures such as the FAB [67]. Therefore, our study underlines the importance of considering education in the interpretation of the performance in executive tools [68]. Higher education levels seem to increase the contact with the evaluation contexts and to contribute to cognitive reserve, exerting a protective effect on the decline associated with healthy aging in EF [69].…”
Section: Discussionsupporting
confidence: 87%
“…This effect has been consistently reported in previous studies with the IFS [33,47,48] but also with other executive screening measures such as the FAB [67]. Therefore, our study underlines the importance of considering education in the interpretation of the performance in executive tools [68]. Higher education levels seem to increase the contact with the evaluation contexts and to contribute to cognitive reserve, exerting a protective effect on the decline associated with healthy aging in EF [69].…”
Section: Discussionsupporting
confidence: 87%
“…Compared with the verbal domain, the visuospatial domain is affected by external intellectual training and education, which needs more complex network processing. 26 This may explain the difference of susceptibility to cerebral microvascular lesions between verbal and visual executive domains. Other studies have also shown that agerelated cognitive decline occurs earlier and more dramatically in the visuospatial domain compared with the verbal domain and that visuospatial executive deficits usually precede typical memory impairments in the prodromal phases of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to testing the results of the main variables, a betweengroup check in terms of age, sleep, coffee intake, and years of education as possible confounding factors (Branco et al, 2014;Buczylowska & Petermann, 2016;Killgore, 2010;Nehlig, 2010) was performed. As these variables were not normally distributed according to the Shapiro-Wilk (S-W) test (all p s > 0.5) a Mann-Whitney test was adopted.…”
Section: Resultsmentioning
confidence: 99%